Impacted porcelain foreign body in the nasopharynx: a clinical enigma (Bangladesh Journal of Otorhinolaryngology, 2011)
Nasopharynx is an exceptionally rare anatomical location for foreign body impaction. We present a unique case of foreign body made of porcelain lodged in the nasopharynx of a one and a half year old child for more than a month. The foreign body had been introduced perorally and had subsequently got impacted in the nasopharynx following amateur digital manipulation. Presence of porcelain foreign body in the nasopharynx has never been reported before. Removal of the foreign body was performed under general anesthesia. This rare situation is potentially dangerous, since its dislodgment may cause fatal airway obstruction. Therefore, in all cases with missing foreign bodies in the aerodigestive system, nasopharyngeal impaction should be kept in mind and examination of the region should be considered. Key Words: Impacted foreign body; nasopharynx; porcelain DOI: http://dx.doi.org/10.3329/bjo.v17i2.8856 BJO 2011; 17(2): 139-143